The effect of tax policy uncertainty on incentivization, managerial effort and total surplus - Alexandra Spaeth (Journal of Business Economics, 2025)
This paper examines the effect of tax policy uncertainty on incentivization and managerial effort in an agency model with risk-averse principal and agent. If the agent's effort is unobservable, the agent's variable share of profit acts as a risk-sharing and incentivizing instrument. Then, a countercyclical tax base policy at the agent level or a procyclical policy at the principal level can increase the agent's variable share of profit, whose increase in turn increases the agent's effort. This theoretical finding favors a procyclical tax policy at the company level (principal) and a countercyclical one at the employee level (agent). Tax policy uncertainty in the sense of tax base risk makes this increase in effort possible and strengthens effects. Additionally, under a countercyclical tax base policy at the agent level, tax base risk at the agent level up to a certain level increases overall utility and thus total surplus.
Keywords: D86; H210; M52; 650; Agency model; Tax base risk; Tax policy uncertainty; Procyclical; Countercyclical